Method of continuous generation grinding tooth surface modification based on electronic gearbox superimposed high-order motion - HAN Jiang; RUI Xiaoyu; TIAN Xiaoqing; YOU Tongfei; LI Guanghui; XIA Lian (Jixie chuandong)
ObjectiveGear tooth surface modification can reduce transmission noise and vibration, and improve load-bearing capacity and service life. However, traditional gear modification only uses drum shape as the constraint condition for modification processing, resulting in significant differences between the gear modification design and the manufacturing. A continuous generation grinding gear surface modification method was proposed based on the combination of electronic gearbox and high-order polynomial interpolation to address this issue.MethodsFirstly, the involute gear surface of the standard cylindrical helical gear was used to model the worm wheel gear surface through coordinate transformation. Then, a continuous generative grinding machining model was established based on the parameter equation of the worm wheel gear surface and the linkage relation with the electronic gearbox. The feed axis of the grinding wheel during the machining process was added with the high-order polynomial motion. Using the normal deviation between the standard involute gear surface and the actual machined gear surface grid points as the evaluation criterion, the Levenberg-Marquardt algorithm was used to optimize the polynomial coefficients of the motion functions of each feed axis of the grinding wheel. Through the polynomial interpolation function of the Siemens 840Dsl CNC system, the practical application of this gear modification method on the Siemens 840Dsl gear grinding machine was discussed.ResultsThe effectiveness and feasibility of the proposed shape modification method have been verified through numerical analysis and test.